Conceptualizing the strategies of representing the image of Russia: History and Evolution (communicative aspects) - E. V. Kolokoltseva (Концепт: философия, религия, культура, 2020)
The paper addresses the issue of the genesis and the evolution of the conceptual formation of the official attitudes toward the principles governing the representation of the Russian Federation and their scientific covering. It appearance in key foreign policy documents and its significance is analyzed with the view to two major conceptual schemes: the international image and the objective perception. Both concepts were examined with comparative research methods. The problems of tracing the current transformations in the official rhetoric to the transformations that are now taking shape in promoting Russia are the factors why this issue is relevant. The particular aspects of the research included the key documents of official bodies endowed with powers to shape foreign policy that were published in the period between 2000 and 2019. The activities of the key institutions and content providers in what concerns international positioning were outlines. Holding and covering mega-events, such as the 2014 Sochi Winter Olympics and the 2018 FIFA World Cup, also served the image needs and, in this respect, was examined in the paper. The concept and method of soft power is introduced for analysis, as it is increasingly efficient and useful in both these respects. The paper concludes with stating that the practice of positive positioning of Russia abroad was substituted in favour of the one of engendering objective perception. The main concern for that consisted in foreign pressure and negative information campaigns, so the decision was a counter measure. In this context, the shift between the two concepts of international promotion is revealed in official documents, having a considerable effect on the communicative potential in terms of acting in accordance with the fundamental values and real attitudes inherent in the Russian culture. Esse quam videri is now not only the national principle, but also the foreign image.